PENGARUH WORKFORCE AGILITY TERHADAP CRISIS MANAGEMENT DENGAN HIGHER ADMINISTRATIVE SUPPORT SEBAGAI VARIABEL MEDIASI - T. Eri Syafrial; Jeni Wardi; Adi Rahmat (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2025)
Crisis management in government is a crucial element for maintaining stability and public trust. Effective crisis management requires good coordination, quick decision-making abilities, and organizational readiness to face sudden challenges. The aim of this research is to determine the effect of Workforce Agility on Crisis Management through Higher Administrative Support as a mediating variable. This research is a type of quantitative research with a causality research design and the population is State Civil Apparatus at the Siak Regency Cooperative and UKM Service Office. with a sample of 44 people. Data collection techniques using questionnaires and distribution using Google Form. The data analysis tool in this research is Structural Equation Modeling (SEM) processed using SmartPLS 3.2.9 for data processing. The results of this research are that Workforce Agility has no effect on Higher Administrative Support, Workforce Agility has a positive and significant effect on Crisis Management, Higher Administrative Support has a positive and significant effect on Crisis Management and Workforce Agility has no effect on Crisis Management through Higher Administrative Support.